Integrasi Nilai Amanah dalam Pelaksanaan Program Makan Bergizi Gratis (MBG) Prabowo-Gibran - Andri Irawan; Putera, Andika Pratama; Nugraha, Muhammad Sandi; Subarna, Ahmad; Ramadhan, Jihan (Penerbit Hellow Pustaka, 2026)
This this research was prompted by the turmoil surrounding the implementation of the Makan Bergizi Gratis (MBG) program. This is a MBG, as one of the government’s priority programs under the leadership of Prabowo-Gibran, has left a number of unresolved issues. One phenomenon that has recently drawn sharp public scrutiny is the occurrence of MBG food poisoning, which has affected many students. It is strongly suspected that these issues stem from the negligence of all parties in upholding a sense of obligation or responsibility while carrying out their governmental duties related to the allocation of MBG in the field. Related the research approach applied in this literature review is qualitative-descriptive, utilizing the library research method. The data was collected from various reliable scientific references to produce a robust and accountable conceptual understanding. Data analysis was conducted using an interpretive-conceptual approach by analyzing the literature and synthesizing the findings. In essence, this study concludes that is: (1) Mapping the understanding of the value of trustworthiness from an Islamic education perspective; (2) The importance of integrating the value of trustworthiness/accountability in performing state duties amidst the implementation challenges of the MBG program in the field; (3) The necessity of reconstructing an SPPG model based on “trust-based management”; and (4) The implications of accountability for the success of national education and nutrition are viewed as an ideal combination that must be fostered over the long term. The findings of this study recommend that the central government implement a much stricter and more effective monitoring system for the distribution of MBG carried out by SPPG and relevant parties in order to minimize the potential for problems.